Dermatological aspects of cerebrovascular diseases - Al-Aboud, Daifullah (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Neurological symptoms are sometimes triggered by the same mechanisms as are skin manifestations. They include genetic conditions like the epidermal nevus syndrome, the Sneddon syndrome, Fabry disease and others, as well as certain inflammatory disorders like erythematous lupus, Behcet disease. Basically all conditions giving rise to anticoagulation processes may cause simultaneously neurological and cutaneous manifestations. Cerebrovascular stroke is the thirdmost common condition of death in the developed world after cancer and ischemic heart disease. The mechanisms responsible for development of skin manifestations in patients afflicted by stroke are shortly reviewed. Stroke may also influence the already existent skin diseases.
Keywords: Cerebral Infarction; Cerebrovascular Disorders; cerebrovaskularne bolezeni; Cerebrovaskularne motnje; dermatologija; koža; Kožne manifestacije; Možganski infarkt; simptomi; Skin Manifestations